NMR spectroscopy as a tool for studying asphaltene composition - Parlov Vuković, Jelena (Array, 2019)
Asphaltenes are the most polar oil components with molecular weights between 500 and 1000 Da, which primarily consist of carbons and hydrogens, some heteroatoms, such as nitrogen, sulphur, oxygen and traces of nickel, vanadium and iron. Owing to their extreme complexity, it is almost impossible to completely identify all the compounds present in asphaltene samples. Various analytical techniques and approaches were used to characterize asphaltenes but their structure and composition are still a matter of thorough investigations. NMR spectroscopy can reveal useful information on asphaltene molecular architecture and aggregation process. In that respect, one- and two-dimensional NMR techniques have widely been employed. Although NMR spectra of these complex mixtures are difficult to interpret, they still can provide valuable data, especially in combination with statistical methods. Some distinctive examples of using NMR spectroscopy to study asphaltenes are given in this review.